Calendar anomalies in Pakistan stock market - Sobia, Quayyoum; Muhammad, Asad; Simonetti, Biagio; Lau, Evan (Universita del Salento, 2017)
Anomalies are those irregularities that cannot be defined by the standard finance theories. In this paper, we examined the existence of an intra-month effect and weekend effect in stock returns of Pakistan stock exchange. Data has been gathered from KSE-100 index which is largest and most liquid stock market in Pakistan. Daily stock index data has been gathered from November 2, 1991, through December 31, 2014, which approximates to about 23 years data. Returns on this data were calculated and calendar anomalies were examined. Our results show that there exists an intra-month effect. Similarly, the existence of the weekend effect in the stock market is also observed. Hence, Karachi stock market shows anomalous behavior in the returns.